Electron ionization mass spectrometry of difurfuryl diamines. Issue 3 (2000) - Lesimple Lesimple, Alain Alain; Le Bigot Le Bigot, Yves Yves; Delmas Delmas, Michel Michel; Banoub Banoub, Joseph Joseph
Abstract : Electron impact mass spectrometry (ei-ms) has aided the structural characterization of a novel series of synthetic difuranic diamines and permitted the comparison with a previous study employing electrospray ionization mass spectrometry. As expected, the molecular radical ion was inexistant in this series of compounds and the fragmentation routes of the molecular radical ion were governed either by homolytic cleavage of the radical R2 or by heterolytic loss of NH3 to give their respective base peaks.